2007
DOI: 10.1086/518047
|View full text |Cite
|
Sign up to set email alerts
|

RAB23 Mutations in Carpenter Syndrome Imply an Unexpected Role for Hedgehog Signaling in Cranial-Suture Development and Obesity

Abstract: Carpenter syndrome is a pleiotropic disorder with autosomal recessive inheritance, the cardinal features of which include craniosynostosis, polysyndactyly, obesity, and cardiac defects. Using homozygosity mapping, we found linkage to chromosome 6p12.1-q12 and, in 15 independent families, identified five different mutations (four truncating and one missense) in RAB23, which encodes a member of the RAB guanosine triphosphatase (GTPase) family of vesicle transport proteins and acts as a negative regulator of hedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
175
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(189 citation statements)
references
References 36 publications
1
175
0
4
Order By: Relevance
“…First, Rice et al recently observed that in mice, loss of the negative regulator in the Hedgehog pathway, Gli3, increased calvarial ossification, resulting in lambdoid synostosis (Rice et al, 2010). In addition, the pan-suture synostosis observed in Carpenter syndrome has recently been discovered to be the result of a RAB23 mutation, another Hedgehog signaling repressor (Jenkins et al, 2007). Taken together, these recent studies suggest that while loss of Hedgehog results in impaired osteogenesis, gain of Hedgehog accelerates intramembranous ossification, and in fact, may cause premature suture fusion.…”
Section: Defining the Etiopathogenesis Of The Ihh 2/2 Calvarial Phenomentioning
confidence: 99%
See 1 more Smart Citation
“…First, Rice et al recently observed that in mice, loss of the negative regulator in the Hedgehog pathway, Gli3, increased calvarial ossification, resulting in lambdoid synostosis (Rice et al, 2010). In addition, the pan-suture synostosis observed in Carpenter syndrome has recently been discovered to be the result of a RAB23 mutation, another Hedgehog signaling repressor (Jenkins et al, 2007). Taken together, these recent studies suggest that while loss of Hedgehog results in impaired osteogenesis, gain of Hedgehog accelerates intramembranous ossification, and in fact, may cause premature suture fusion.…”
Section: Defining the Etiopathogenesis Of The Ihh 2/2 Calvarial Phenomentioning
confidence: 99%
“…Recently, increased Hedgehog activity via loss of natural repressors has been observed to result in craniosynostosis, both in mouse models (Rice, 2008) and clinically (Jenkins et al, 2007). Shh is expressed in developing cranial bones (Kim et al, 1998), but its functional role in this tissue has not been evaluated as Shh 2/2 embryos die before the onset of cranial osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Rab23, identified by the Anderson lab with other cilia mutants affecting Shh signaling, renders the Shh pathway constitutively active when lost [33,34]. Consistent with this mouse phenotype, human Rab23 mutations have also been found in Carpenter syndrome that causes craniosynostosis, polysyndactyly, obesity, and cardiac defects [35]. Shh pathway analysis demonstrates that Rab23 plays a minor role in promoting Gli3 cleavage to form Gli3 repressor but has a critical role in preventing the accumulation of the Gli1 and Gli2 activators [33].…”
Section: A "Rab-id" Transit System Controls Membrane Shape and Movementmentioning
confidence: 80%
“…1,2 The cardinal features of this syndrome are acrocephaly with variable synostosis of the sagittal, lambdoid, and coronal sutures; peculiar facies; brachydactyly of hands with syndactyly; preaxial polidactyly and syndactyly of the feet; congenital heart defects; growth retardation; mental retardation; hypogenitalism and obesity. [1][2][3][4][5] Besides common clinical manifestations, cerebral malformations, oral and dental abnormalities, coxa valga, genu valgum, hydronephrosis, precocious puberty and hearing loss may be seen. [1][2][3][4][5][6][7][8][9][10][11][12] Variable rare abnormalities may also accompany the major clinical findings.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Besides common clinical manifestations, cerebral malformations, oral and dental abnormalities, coxa valga, genu valgum, hydronephrosis, precocious puberty and hearing loss may be seen. [1][2][3][4][5][6][7][8][9][10][11][12] Variable rare abnormalities may also accompany the major clinical findings. 1 However, to the best of our knowledge, situs inversus totalis has not been demonstrated previously in Carpenter syndrome.…”
mentioning
confidence: 99%